Compact Multilayer Film Structure for Angle Insensitive Color Filtering - Yang, Chenying (Sci Rep, 2015)
Here we report a compact multilayer film structure for angle robust color filtering, which is verified by theoretical calculations and experiment results. The introduction of the amorphous silicon in the proposed unsymmetrical resonant cavity greatly reduces the angular sensitivity of the filters, which is confirmed by the analysis of the phase shift within the structure. The temperature of the substrate during the deposition is expressly investigated to obtain the best optical performance with high peak reflectance and good angle insensitive color filtering by compromising the refractive index of dielectric layer and the surface roughness of the multilayer film. And the outlayer of the structure, worked as the anti-reflection layer, have an enormous impact on the filtering performance. This method, described in this paper, can have enormous potential for diverse applications in display, colorful decoration, anti-counterfeiting and so forth.